Sabar dan Shalat dalam Tafsir Al-Baqarah Ayat 45-46: Sabar dan Shalat dalam Tafsir Al-Baqarah ayat 45-46 - Budi Damayanti, Lany; Ghafur, Abdul (Ulumuna: Jurnal Studi Keilsman, 2024)
Patience (sabar) is a crucial moral quality emphasized in the Quran, mentioned over a hundred times in both Makki and Madani surahs. Scholars like Al-Ghazali, Ibn al-Qayyim, and Abu Thalib al-Makki have highlighted its importance, with Al-Ghazali noting it appears seventy times and Ibn al-Qayyim around ninety times. Patience encompasses various meanings, including restraint, endurance, and perseverance. Given its prevalence in the Quran and its fundamental significance in Islam, particularly in Surah Al-Baqarah verses 45-46, this study aims to explore the concept of patience within these verses using a tahlili tafsir method and literature review approach. It draws from several tafsir texts and journals for reference, while also addressing the asbabun nuzul (causes of revelation) and the grammar of the verses. The analysis reveals that patience is not merely about self-restraint but also involves strong hope and steadfastness. Both patience and prayer serve as sources of spiritual strength, bringing peace to the soul and enhancing one's closeness to Allah.